A role for PDGF-C/PDGFRα signaling in the formation of the meningeal basement membranes surrounding the cerebral cortex - Johanna Andrae (Biology Open, 2016)
Platelet-derived growth factor-C (PDGF-C) is one of three known ligands for the tyrosine kinase receptor PDGFRα. Analysis of Pdgfc null mice has demonstrated roles for PDGF-C in palate closure and the formation of cerebral ventricles, but redundancy with other PDGFRα ligands might obscure additional functions. In search of further developmental roles for PDGF-C, we generated mice that were double mutants for Pdgfc−/− and PdgfraGFP/+. These mice display a range of severe phenotypes including spina bifida, lung emphysema, abnormal meninges and neuronal over-migration in the cerebral cortex. We focused our analysis on the central nervous system (CNS), where PDGF-C was identified as a critical factor for the formation of meninges and assembly of the glia limitans basement membrane. We also present expression data on Pdgfa, Pdgfc and Pdgfra in the cerebral cortex and microarray data on cerebral meninges.